التكيف النفسي الاجتماعي لدى طلبة صعوبات القراءة في دولة الكويت وعلاقته بالتحصيل الدراسي - الشرهان، فواز عادل Alsharhan, Fawwaz Adel (جامعة القاهرة - كلية الدراسات العليا للتربية, 2020)
تظل صعوبات التعلم هي واحدة من القضايا التي تلفت اهتمام الباحثين والدارسين، حيث يظل يتناولها الباحثين في أبحاثهم ومنشوراتهم حتى يستطيعوا تطوير حل وعلاج المشاكل التعليمية والنفسية الاجتماعية التي تنتج عن صعوبات التعلم، وتعد صعوبات القراءة واحدة من أشكال صعوبات التعلم بل هي من أشهرها كونها تصيب نسبة كبير من أطفال وطلاب صعوبات التعلم، ومن الجدير بالذكر أن صعوبات التعلم تكون لها أعراض تعليمية أكاديمية تظهر على الطلاب من ضمنها ضعف التحصيل الدراسي وأيضا الخجل وعدم التكيف النفسي الاجتماعي مع ذويهم وأفراد المجتمع كونهم يشعرون بالنبذ والاختلاف، ونسبة طلاب صعوبات القراءة كبيرة في دولة الكويت ويظل الباحثين يبحثون عن طرق متنوعة لحل المشاكل النفسية والاجتماعية الناتجة عنها. لذلك جاءت هذه الدراسة بهدف التعرف على مدى التكيف النفسي الاجتماعي لدى عينة من طلاب ذوي صعوبات القراءة في دولة الكويت والتعرف على طرق علاج الخجل وتدني مستوى التكيف النفسي الاجتماعي لديهم، وتكونت عينة الدراسة من عدد (٥٠) طالب من ذوي صعوبات القراءة القانطين بمختلف المحافظات والمناطق بدولة الكويت، وقد أتبع الباحث المنهج الوصفي التحليلي كونه واحد من أهم المناهج التي يتم أتباعها في الأبحاث النظرية الميدانية التي تتطلب حصر آراء العينة البحثية. أما عن أدوات الدراسة فقد استعان الباحث بالكتب المصورة والإلكترونية والمراجع المنشورة التي تتناول نفس الموضوع حتى يتم كتابة الإطار النظري؛ وأداة الاستبيان الإلكتروني التي سيتم توزيع أسئلة الدراسة عليهم ثم سحبها على برنامج الـ SPSS لتحليل الإجابات إحصائيا وبيانيا. وقد أشارت تلك الدراسة في نتائجها أن الطلاب ذوي صعوبات التعلم لديهم نسبة كبيرة جداً من الخجل والشعور بالنبذ الفردي كن أفراد المجتمع وعدم اندماجهم اجتماعيا في المجتمع الفصلي التعليمي والمدرسي، كما أشارت الدراسة إلى أن هناك علاقة قوية بين ضعف التحصيل الدراسي وعدم التكيف الاجتماعي النفسي لذوي طلاب صعوبات القراءة في دولة الكويت.
Learning disabilities remain one of the issues that fill the mind of researchers and learners in the field of Special Education. As researchers continue to address these issues in their research and publications so that they can develop or solve the educational and psychosocial problems that result from learning difficulties. Reading difficulties are one of the forms of learning difficulties but it is one of the most famous because it affects a large proportion of children and students with learning difficulties. It is worth noting that the students of learning difficulties have academic educational symptoms that appear on them, including poor academic achievement, as well as shyness and lack of psychosocial adaptation with their families and members of society, as they feel excluded and different. The percentage of students with reading difficulties is large in the State of Kuwait and the researchers continue to search for various ways to solve the psychological and social problems that result from these difficulties. Therefore, this study came with the aim of identifying the extent of psychosocial adaptation among a sample of students with reading difficulties in the State of Kuwait and identifying methods of treating shyness and their low level of psychosocial adaptation. The study sample consisted of (50) students with reading difficulties living in the various governorates and regions in the State of Kuwait. The researcher followed the descriptive analytical approach as it is one of the most important approaches that are followed in theoretical field research that requires restricting the opinions of the research sample. As for the study tools, the researcher has used picture and electronic books and published references dealing with the same topic in order to write the theoretical framework, and the electronic questionnaire tool that the study questions will be distributed to them and then pulled into the SPSS program to analyze the answers statistically and graphically. This study indicated in its results that students with reading difficulties have a very large percentage of shyness and a feeling of individual exclusion from community members and their lack of social integration in the classroom educational and school community. The study also indicated that there is a strong relationship between poor academic achievement and the lack of socio-psychological adaptation for students with reading difficulties in the State of Kuwait.
Keywords: التربية الخاصة -- الإرشاد النفسي -- التكيف الاجتماعي -- عسر القراءة -- صعوبات التعلم -- التحصيل المعرفي -- طلبة المدارس